The Pleasure Evoked by Sad Music Is Mediated by Feelings of Being Moved - Vuoskoski, Jonna K.; Eerola, Tuomas (Frontiers in Psychology, 2017)
Why do we enjoy listening to music that makes us sad? This question has puzzled music psychologists for decades, but the paradox of “pleasurable sadness” remains to be solved. Recent findings from a study investigating the enjoyment of sad films suggest that the positive relationship between felt sadness and enjoyment might be explained by feelings of being moved (Hanich et al., 2014). The aim of the present study was to investigate whether feelings of being moved also mediated the enjoyment of sad music. In Experiment 1, 308 participants listened to 5 sad music excerpts and rated their liking and felt emotions. A multilevel mediation analysis revealed that the initial positive relationship between liking and felt sadness (r = .22) was fully mediated by feelings of being moved. Experiment 2 explored the interconnections of perceived sadness, beauty, and movingness in 27 short music excerpts that represented independently varying levels of sadness and beauty. Two multilevel mediation analyses were carried out to test competing hypotheses: A) that movingness mediates the effect of perceived sadness on liking, or B) that perceived beauty mediates the effect of sadness on liking. Stronger support was obtained for Hypothesis A. Our findings suggest that – similarly to the enjoyment of sad films – the aesthetic appreciation of sad music is mediated by being moved. We argue that felt sadness may contribute to the enjoyment of sad music by intensifying feelings of being moved.